Nomenclatural validation of three North American species of Heliothinae (Lepidoptera: Noctuidae) and the adult description of Heliolonche joaquinensis Hardwick - Pogue, Michael G. (Zootaxa, 2006)
Article 13.1.1 of the International Code of Zoological Nomenclature states that names published after 1930 must have a description that defines and differentiates the taxon with characters. Three species of Heliothinae described by Hardwick (1996) are not in conformance with this Article; thus, they are nomina nuda. The following species are validated by descriptions and illustrations of the adult and genitalia: Schinia angulilinea new species (= S. arizonensis Hardwick), S. maculata new species (= S. blanca Hardwick), and S. erythrias new species (= S. pulchra Hardwick). The adult of Heliolonche joaquinensis Hardwick is described, along with illustrations of the adult and genitalia.